Reliability and validity of the Thai Drug Hypersensitivity Quality of Life Questionnaire: a multi-center study - Yuda Chongpison (2020)
© 2018 The Author(s) 2018. Published by Oxford University Press in association with the International Society for Quality in Health Care. All rights reserved. Objective: To adapted the Drug Hypersensitivity Quality of Life (DrHy-Q) Questionnaire from Italian into Thai and assessed its validity and reliability. Design: Prospectively recruited during January 2012-May 2017. Setting: Multicenter; six Thai tertiary university hospitals. Study Participants: Total of 306 patients with physician-diagnosed drug hypersensitivity. Interventions: Internal consistency and test-retest reliability were evaluated among 68 participants using Cronbach's ? and intra-class correlation coefficient (ICC). The validity of Thai DrHy-Q was assessed among 306 participants who completed World Health Organization Quality of Life-BREF (WHOQOL-BREF-THAI). Construct and divergent validities were assessed for Thai DrHy-Q. Known-groups validity assessing discriminating ability was conducted in Thai DrHy-Q and WHOQOL-BREF-THAI. Main outcome measures: Validity; reliability; single vs. multiple drug allergy; non-severe cutaneous adverse reactions (SCAR) vs. SCAR. Results: Thai DrHy-Q showed good reliability (Cronbach's ? = 0.94 and ICC = 0.8). Unidimensional factor structure was established by confirmatory factor analysis (CFI&TLI = 0.999, RMSEA = 0.02). Divergent validity was confirmed by weak correlation between Thai DrHy-Q and WHOQOL-BREF-THAI domains (Pearson's r = -0.41 to -0.19). Known-groups validity of Thai DrHy-Q was confirmed with significant difference between patients with and without life-threatening SCAR (P = 0.02) and patients with multiple implicated drug classes vs. those with one class (P < 0.01); while WHOQOL-BREF-THAI could differentiate presence of life-threatening SCAR (P < 0.01) but not multiple-drug allergy. Conclusions: Thai DrHy-Q was reliable and valid in evaluating quality of life among patients with drug hypersensitivity. Thai DrHy-Q was able to discriminate serious drug allergy phenotypes from non-serious manifestations in clinical practice and capture more specific drug-hypersensitivity aspects than WHOQOL-BREF-THAI.